THE STUDY OF DETERMINANTS OF CAPITAL STRUCTURE: EVIDENCE FROM UK PANEL DATA - Singal, Ankur (2012)
The paper examines the determinants of capital structure of firms listed on FTSE 350 over a period from 2002 to 2011 using panel data. The sample of this study involves 178 listed firms from nine different industries. Several theories of capital structure are reviewed in order to achieve the testable hypothesis regarding the capital structure decision of UK based firms. To test the hypothesis we have utilised pooled ordinary least square, random effects, fixed effects models and ANOVA test. Our results suggest that profitability and firm size are positively related to both long-term and short-term leverage. Whereas, growth opportunities and earning volatility is negatively related to both type of gearing ratio. Tangibility is negatively associated with short-term leverage and positively related to long-term leverage. The presence of non-debt tax shield has a positive impact in short-term leverage and opposite effect in the long-run. Overall, from the results we can say that firm size and profitability shows significant relation with both the gearing ratios and non-debt tax shield with short-term leverage and growth with long-term leverage. Hence, these independent variables have statistically significant impact on the capital structure of the UK based firms.